International Activities in the Field of Language Technologies and Resources - A. B. Antopolsky (Informaciâ i Innovacii)
Describes the international organizations active in the field of language technologies and resources, as well as the projects they are implementing. The following areas are highlighted: computational linguistics in general, support for endangered languages, terminology and translation activities, standardization. Highlighted organizations and projects working in the technology of the Semantic Web and related open data. Organizations and projects in the field of language technologies and resources in Europe are considered separately.